2015
DOI: 10.1007/s10461-014-0985-7
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Theory-Driven Text Messages is Associated with HIV Risk Reduction Among Methamphetamine-Using Men Who have Sex with Men

Abstract: Fifty-two non-treatment-seeking methamphetamine-using men who have sex with men were enrolled in Project Tech Support, an open-label pilot study to evaluate whether exposure to theory-based [social support theory (SST), social cognitive theory (SCT), and health belief model (HBM)] text messages could promote reductions in HIV sexual risk behaviors and/or methamphetamine use. Multivariable analyses revealed that increased relative exposure to HBM or SCT (vs. SST) text messages was associated with significant re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 51 publications
0
48
0
Order By: Relevance
“…Results from only one recent large efficacy trial of a technology-based HIV risk reduction intervention for drug users [35] showed that those receiving a computerized intervention demonstrated higher HIV testing rates than those in the attention control; however, no differences in sex risk was found. Earlier studies showed that tailored text messages reduced HIV risk behavior among methamphetamine users [48, 49]. Nonetheless, there continues to be a clear need for larger trials to establish the efficacy of different technology-based approaches (e.g., text, mobile app) for a variety of drug-using populations (i.e., heroin users vs. stimulant users).…”
Section: Resultsmentioning
confidence: 99%
“…Results from only one recent large efficacy trial of a technology-based HIV risk reduction intervention for drug users [35] showed that those receiving a computerized intervention demonstrated higher HIV testing rates than those in the attention control; however, no differences in sex risk was found. Earlier studies showed that tailored text messages reduced HIV risk behavior among methamphetamine users [48, 49]. Nonetheless, there continues to be a clear need for larger trials to establish the efficacy of different technology-based approaches (e.g., text, mobile app) for a variety of drug-using populations (i.e., heroin users vs. stimulant users).…”
Section: Resultsmentioning
confidence: 99%
“…The theory and evidence underlying the self-monitoring for selfmanagement hypothesis was based on psychological research findings that self-monitoring and reactivity to self-monitoring supported self-regulation and behavior change (Bandura, 1991; Carver, 1979; Kanfer, 1970; Kazdin, 1974). Social Cognitive Theory, Theory of Reasoned Action, Theory of Planned Behavior, and the Health Belief Model are the foundation of many extensively used interventions with mobile phone applications and text-messaging technology (Reback, Fletcher, Shoptaw, & Mansergh, 2015; Swendeman, Comulada, Ramanathan, Lazar, & Estrin, 2015; Swendeman, Ramanathan, et al, 2015).…”
mentioning
confidence: 99%
“…This team has also demonstrated efficacy of texting to reduce sexual risk behaviors and substance use with high-risk gay and bisexual men [58][59][60][61] and with HRY [55,62]. Meta-analyses evaluating the efficacy of texting informational, motivational, and resource referral content found benefits for behavior changes when the studies are sufficiently powered [50,63].…”
Section: Automated Messaging and Monitoring Intervention (Ammi)mentioning
confidence: 98%
“…In addition, two peer support interventions with men who have sex with men conducted via Facebook groups over twelve weeks found increased requests for HIV home test kits in Los Angeles [98] and increased clinic-based HIV testing in Peru [99]. Similarly, Reback and colleagues [59,100] found that peer support via text messaging for eight weeks reduced substance use and sexual risk behaviors among methamphetamine-using men who have sex with men. Adolescence, in particular, is a developmental period where the influence of peers is crucial [101].…”
Section: Peer Support Via Social Mediamentioning
confidence: 99%
See 1 more Smart Citation